Repairing tendon-exposed wounds by combing the Masquelet technique with dermoplasty - Yao, Jiangling; Zeng, Yunfu; Yang, Jian; Wu, Qian; Chen, Liying; Zheng, Linyang; Wang, Rong; Zhu, Hengjie; Cui, Hongwang; Huang, Yuesheng; Cheng, Shaowen (Frontiers in Surgery, 2022)
Background: Wound repair is a new field that has emerged in China in the last five years. Exposed tendon wounds are one of the most common problems faced in wound treatment today, as the poor blood supply leads to low survival rates of skin grafts. This paper explores the feasibility of applying the Masquelet technique to repair tendon-exposed wounds. Method: We examined 12 patients with tendon-exposed wounds, 5 males and 7 females, from January 2021 to November 2021, including 2 patients with post-traumatic wounds, 8 diabetic patients with dorsal wounds, and 2 patients with various chronic infections. The Masquelet technique was employed to treat these wounds. The wound surface was sealed with antibiotic bone cement to form an induction membrane, the cement was removed after 3-4 weeks, and the wound was repaired with skin grafts to observe survival, appearance, texture, healing, and related functions. Results: All wounds were covered with antibiotic bone cement, and after 3-4 weeks, an induction membrane was applied, and in 10 out of 12 patients, full-thickness skin grafts were applied, and the patients survived. However, in 2 patients, the skin became partially necrotic, but these patients recovered by changing medications. Conclusions: The current study found that direct skin grafting may effectively treat exposed tendon wounds once the Masquelet approach generates the induction membrane. Further, this method is less difficult, less expensive, and easier to care for the procedure that deserves to be used more frequently.